Uganda - Moving Beyond Recovery : Investment and Behavior Change, For Growth, Volume 1. Summary and Recommendations - World Bank (Washington, DC, 2012)
In 2006 most of the people of Uganda, with the notable exception of those in the conflict-blighted Northern Region, enjoy a better quality of life and brighter opportunities in a stable and growing economy. Uganda's economy has bounced back beyond what could be regarded as recovery, with real incomes per person now exceeding the levels reached at Independence in 1962. The report structure is as follows: volume one synthesizes the conclusions from analysis in Volume two. In Chapter 1 of Volume two, emphasis is placed on understanding what drove past growth at macro and sector levels, and in particular, on how Uganda's firms and farms have evolved. Chapter 2 continues the retrospective of past growth in agriculture, the most important sector of the economy. The report provides a comprehensive review of growth trends in agriculture, using several data sources. The chapter provides fresh insights on recent trends in poverty and inequality. Chapter 3 presents growth diagnosis and it identifies short-term actions to remove emerging constraints to present and near-term future growth. Chapter 4 models alternative future growth paths and the impact o f alternative public investments on growth using a SAM-based CGE model. The analysis reveals there is little to be gained from 'robbing Peter to pay Paul' for example fixing infrastructure by reducing education financing. Chapters 6 and 7 return to the short-term priorities to remove binding constraints to growth, and put meat on the actions identified in Chapter 3 as being required in the financial sector (Chapter 6) and in infrastructure (Chapter 7). Finally, Chapter 8 ends by assessing the scope for an externally financed scale up of infrastructure.